A companion to rock art - McDonald, Jo (Josephine); Veth, Peter Marius (Malden, MA : Wiley-Blackwell, 2012)
"This unique guide provides an artistic and archaeological journey deep into human history, exploring the petroglyphic and pictographic forms of rock art produced by the earliest humans to contemporary peoples around the world. Summarizes the diversity of views on ancient rock art from leading international scholars Includes new discoveries and research, illustrated with over 160 images (including 30 color plates) from major rock art sites around the world Examines key work of noted authorities (e.g. Lewis-Williams, Conkey, Whitley and Clottes), and outlines new directions for rock art research Is broadly international in scope, identifying rock art from North and South America, Australia, the Pacific, Africa, India, Siberia and Europe Represents new approaches in the archaeological study of rock art, exploring issues that include gender, shamanism, landscape, identity, indigeneity, heritage and tourism, as well as technological and methodological advances in rock art analyses "--
"Represents new approaches in the archaeological study of rock art, exploring issues that include gender, shamanism, landscape, identity, indigeneity, heritage and tourism, as well as technological and methodological advances in rock art analyses"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Petroglyphs -- Handbooks, manuals, etc; Rock paintings -- Handbooks, manuals, etc; SOCIAL SCIENCE -- Archaeology; Petroglyphs; Rock paintings; Electronic books; Handbooks and manuals; Handbooks and manuals; Electronic books